2008
DOI: 10.1080/10599240802454528
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Strategy and 24-Hour Biomonitoring of Paraquat in Agricultural Workers

Abstract: The objectives of this study were to recruit agricultural workers in Costa Rica to participate in a 24-hour urine collection for paraquat exposure assessment and to compare the 24-hour sampling to endof-shift sampling. The authors recruited 187 handlers and 54 nonhandlers from coffee, banana, and palm oil plantations. The completeness of 24-hour urine samples collected (a total of 393 samples) was confirmed by questionnaire and urinary creatinine level. For a subset of 12 samples, the absorbed paraquat level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Nevertheless, this study quantified biomarkers in urine, which was not often done in previous studies. It is important to remember that previous evidence has found that quantifying paraquat in a single micturition after exposure, as done by the present study, is highly correlated with quantifications using samples of 24-h urine 24) . Bias related to the health of the workers may also exist given the method used to recruit participants.…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, this study quantified biomarkers in urine, which was not often done in previous studies. It is important to remember that previous evidence has found that quantifying paraquat in a single micturition after exposure, as done by the present study, is highly correlated with quantifications using samples of 24-h urine 24) . Bias related to the health of the workers may also exist given the method used to recruit participants.…”
Section: Discussionsupporting
confidence: 74%